Obstetric practices in childbirth care and usual risk birth - Natália de Abreu Alcântara; Thais Jormanna Pereira Silva
Abstract Objectives: to analyze the incidence of obstetric practices in labor and childbirth care at usual risk in a tertiary hospital. Methods: cross-sectional, descriptive study with a quantitative approach. Data were collected from 314 Monitoring Sheets of Labor and Childbirth Care of women who had their birth attended at the institution, from July 2017 to July 2018. The study was approved by the research ethics committee, with the embodied opinion number 2.822.707. Results: most women in the study were between 20 and 34 years old, coming from the city of Fortaleza, Ceará; had completed high school; and had unpaid work. The prevalence of good practices was identified: umbilical cord clamping in a timely manner (81.5%), immediate skin-to-skin contact (73.9%), breastfeeding in the childbirth room (74.2%), freedom of position and movement (72.3%), completion of the partograph (66.6%), presence of a companion (66.2%), offer of a liquid diet (65%), and non-pharmacological methods for pain relief (54.8%). As for interventional practices, we identified: venoclysis (42.4%), oxytocin infusion (29%), and amniotomy (11.1%). Conclusions: advances in the adoption of good practices based on scientific evidence are noteworthy; however, the technocratic model of childbirth care for women at normal risk persists.